Experimental study of two mooring systems for wave energy converters - Sheng Xu (2018)
Model tests have been conducted to study the performance of alternative mooring systems aimed to be used at a later stage in a wave energy converter under development. The initial set of tests are intended to establish the properties of single lines of different configuration and thus a simple buoy has been chosen as the floater. Two mooring systems have been tested: a traditional catenary mooring system and a hybrid mooring system that behaves as a slack system. The performance of both mooring systems have been addressed by comparing the measured buoy motions in six degrees of freedom and mooring line tension, under regular and irregular head waves. In terms of mean drift motions, the obtained results demonstrated that the catenary mooring system may perform better for the operational conditions, while the slack system gave better results for the survival conditions. Regarding mooring line tensions in irregular seas, the slack system provides significantly lower spectral peaks.